2019
DOI: 10.1159/000500941
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Nomogram for Pancreatic Stone Formation in Chronic Pancreatitis over a Long-Term Course: A Cohort of 2,153 Patients

Abstract: Background: Pancreatic stones are pathognomonic of chronic pancreatitis (CP). This study aimed to determine the incidence, identify risk factors, and develop a nomogram for pancreatic stones in CP patients. Methods: Patients with CP admitted to our center from January 2000 to December 2013 were enrolled. Cumulative rates of pancreatic stones after the onset of CP and after the diagnosis of CP were calculated. Patients were randomly assigned, in a 2: 1 ratio, to the training and validation cohort. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The formation of PD stones takes time. Studies have shown that more than 50% of patients with CP developed PD stones 8 years after the first AP onset, 22 and the median time from the first AP attack to the formation of PD stones was 103.58 months for patients in group C (data not shown). However, 41.7% of patients in group A presented with PD stones at the first visit, which indicated that there had been some unknown mechanism during the PD stones formation for patients in group A.…”
Section: Discussionmentioning
confidence: 91%
“…The formation of PD stones takes time. Studies have shown that more than 50% of patients with CP developed PD stones 8 years after the first AP onset, 22 and the median time from the first AP attack to the formation of PD stones was 103.58 months for patients in group C (data not shown). However, 41.7% of patients in group A presented with PD stones at the first visit, which indicated that there had been some unknown mechanism during the PD stones formation for patients in group A.…”
Section: Discussionmentioning
confidence: 91%